Lanthanide organic frameworks for luminescence sensing of nitrobenzene and nitrophenol with high selectivity. (August 2017) - Sun, Zan; Hu, Peng; Ma, Yue; Li, Licun
Abstract: A series of lanthanide(III)–organic frameworks, namely {[Ln2 (L)3 (H2 O)4 ]· 10H2 O}n (Sm1, Eu2, Gd3, Tb4, Dy5 and Ho6, H2 L = 5-(pyridine-4-ylmethoxy)isophthalic acid) have been synthesized under solvothermal conditions. Compounds1 –6 are isostructural and exhibit an interesting 3D pcu topology with binuclear [Ln2 (CO2 )6 ] units as 6-connected nodes, and free water molecules are filled in 3D coordination frameworks through hydrogen-bonding interactions. Compound4 can be used as a fluorescent probe for sensing nitroaromatic compounds with high sensitivity and selectivity based on luminescence quenching effects arising from host−guest interactions in DMF system. In particular, compound4 can sense nitrobenzene (NB) and nitrophenol isomers (2-, 3- and 4-NP) simultaneously. Thus, this material can be potentially used as a luminescent sensor for nitroaromatic compounds. Graphical abstract: A series of Ln MOFs based on the binuclear units have been obtained. Tb MOF can sense 4-nitrophenol with high sensitivity and selectivity. Highlights: A series of Ln-MOFs are obtained and exhibit an interesting 3D pcu topology. Tb compound can sense nitrobenzene and 2-, 3- and 4-nitrophenol simultaneously. Tb material may be an excellent luminescent sensor for nitroaromatic compounds.